2002
DOI: 10.1007/bf02478930
|View full text |Cite
|
Sign up to set email alerts
|

Tracking cell invasion of human glioma cells and suppression by anti-matrix metalloproteinase agent in rodent brain-slice model

Abstract: Persistent expression of green fluorescent protein (GFP) in human malignant glioma cell clones (U87MG, U251MG, and U373MG) was established using the pEGFP-Cl vector. Tumor spheroid was implanted into the caudate nucleus-putamen of a severely compromised immunodeficient (SCID) mouse brain slice. To allow quantitative assessment of tumor cell invasion, the invasion area index was measured on days 1, 3, 5, and 7 by a fluorescence stereomicroscope and an image analyzer in the presence of varying concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It proves to be useful in studying both physiological and pathophysiological developmental processes. For example, it has been previously used in studying mechanisms of invasion in glioma and astrocytoma cells [Matzner et al, 1992; Ohnishi et al, 1998; Jung et al, 2001; Yoshida et al, 2002]. In our case, this model can create co‐culture settings between melanoma cells and the brain tissue environment that allows for more realistic growth settings yet being relatively easy to manipulate for treatment.…”
Section: Discussionmentioning
confidence: 98%
“…It proves to be useful in studying both physiological and pathophysiological developmental processes. For example, it has been previously used in studying mechanisms of invasion in glioma and astrocytoma cells [Matzner et al, 1992; Ohnishi et al, 1998; Jung et al, 2001; Yoshida et al, 2002]. In our case, this model can create co‐culture settings between melanoma cells and the brain tissue environment that allows for more realistic growth settings yet being relatively easy to manipulate for treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Functionally, inhibitors of metalloproteinase activity attenuate the growth of glioma cells implanted into the flank (43) or brain of mice (44). Impressively, parenterally given inhibitors of metalloproteinase activity reduce the spread and size of intracranial gliomas in rodents (45).…”
Section: Discussionmentioning
confidence: 99%
“…9,10,16,51,64,77,82,84,95,96 Nonetheless, it seems that glioma resection should be the most extensive possible to have a real impact on the natural history of this kind of tumor. 9,16 Furthermore, it has been well demonstrated that gliomas migrate along myelinated fiber tracts of white matter, 6,41,42,52, 59,81,108 in particular, with frequent invasion of the corpus callosum and thus with a risk of contralateral dissemination. 70 Despite many reports concerning callosotomy as a treatment in some kinds of intractable epilepsy 46,56,[66][67][68]71,85,87,89,91,93,99,104 or as a route to the ventricular system 2,7,103 no specific work is, to our knowledge, currently dedicated to the study of surgical outcome following resection of the corpus callosum invaded by glioma.…”
mentioning
confidence: 98%